Goodwill Impairment : An Empirical Investigation of Write-Offs under SFAS 142 - Sellhorn, Thorsten (Bern Peter Lang International Academic Publishing Group, 2018)
In 2001, goodwill amortization in the US was eliminated in favor of an impairment-only approach, which, according to critics, gives managers vast discretion and opportunities for earnings management. Prior research suggests that discretionary asset write-offs are associated with economic factors and managers financial reporting objectives. Based on a systematic literature review, this study investigates for a comprehensive sample of US firms the determinants of goodwill write-off behavior. Regression analysis shows that write-off behavior is significantly explained by firms economic properties. Only in large, high-profile firms, incentives appear to be significant determinants. These findings suggest that the impairment-only approach does capture goodwill impairment at least to some extent.
English
Keywords: Accounting: study & revision guides; Budgeting & financial management; Bilanzpolitik; Empirical; Firmenwert; Generally Accepted Accounting Principles; Geschäftswert; Goodwill; Goodwill; Impairment; Impairment; Investigation; Offs; Sellhorn; SFAS; under; USA; US-GAAP; Wertberichtigung; Write